Impact of malocclusion on oral health-related quality of life of preschool children - ROSA,Guilherme Nascimento da (2015)
OBJECTIVE: This study assessed the relationship of dental malocclusion with COHRQoL considering socioeconomic backgrounds and clinical factors. METHODS: A survey was carried out in Santa Maria, Brazil, during the National Children's Vaccination Day. The sample comprised 478 children aged 12 to 59 months. Fifteen trained and calibrated examiners evaluated the presence of anterior malocclusion traits (AMT) - anterior open bite, overjet and sealing lip. COHRQoL was measured through overall scores of the Brazilian version of ECOHIS (Early Childhood Oral Health Impact Scale). The assessment of association used adjusted Poisson regression models. RESULTS: The unadjusted assessment observed age, untreated dental caries and anterior open bite as the main covariates of the overall ECOHIS score. After the adjustment, the presence of anterior open bite had a negative impact on COHRQoL. There was no association between overjet and sealing lip with COHRQoL. CONCLUSION: In conclusion, anterior open bite present a negative impact on COHRQoL.